Analysis on the Man-Machine-Environment Collaborative Teaching Method for Mining Engineering Major - Liu, Lang; Sun, Xuehua; Song, Ki-il (International Journal of Emerging Technologies in Learning (iJET), 2016)
Man, teaching equipment (machine), and teaching environment in the higher education system constitute the man–machine–environment system in the teaching system. In this study, modern higher pedagogy is combined with man–machine–environment system engineering. The teaching system is analyzed in the point of view of mining engineering profession and a new type of “man-machine-environment collaborative teaching method” is proposed. Also, we conducted a comprehensive discussion about the academic problems in various aspects of composition, theoretical basis, and functional allocation by combining teaching reform features of the mining engineering profession. The practice of man–machine–environment collaborative teaching method strengthens students’ learning of perceptual knowledge, alleviates difficulty of site visit and practice, and enables conducting an indoor interactive dynamic simulation experiment. Moreover, it cultivated the students’ operational ability, spatial thinking, and global concept of industrial mining sites. Furthermore, it improved the autonomous learning ability of undergraduates, which was of great significance to cultivating innovative talents. Lastly, it transformed the teaching method from “teaching” to initiative “exploration” and “discovery” for students.